The Implementation of Child Custody After Divorce in Nglorog Village, Temanggung: The Implementation of Child Custody After Divorce in Nglorog Village, Temanggung - Eka Mahargiani Rokhma; Binti Isnaini; Fatmawati Sungkawaningrum (Jurnal Syariah, Hukum, dan Ekonomi Islam, 2025)
This study examines post-divorce child custody (ḥaḍānah) practices in Nglorog Village, Pringsurat District, Temanggung Regency, from the perspective of Maqāṣid al-Sharīʿah. Divorce is often regarded as a last resort for couples facing irreconcilable marital conflict; however, it entails significant consequences for children, who are particularly vulnerable to psychological distress, declining academic performance, and social challenges. Therefore, examining child custody arrangements is essential to safeguarding children’s welfare and future well-being. In Islamic law, Maqāṣid al-Sharīʿah emphasizes the protection of five fundamental values: religion (ḥifẓ al-dīn), life (ḥifẓ al-nafs), intellect (ḥifẓ al-ʿaql), lineage (ḥifẓ al-nasl), and property (ḥifẓ al-māl). In the context of child custody, the protection of life, intellect, and lineage is particularly relevant. This research employs a qualitative descriptive approach, with data collected through in-depth interviews involving religious leaders, village officials, divorced parents, and local social institutions. The findings reveal that divorce has complex impacts on children, especially when post-divorce parenting is inconsistent or unbalanced. Nevertheless, several stakeholders have sought to incorporate Maqāṣid al-Sharīʿah values in determining custodial arrangements by prioritizing children’s best interests, emotional stability, and education. Accordingly, Maqāṣid al-Sharīʿah functions not only as a normative Islamic legal framework but also as an ethical foundation for ensuring fair and proportionate child custody practices after divorce.